Răspuns :
2 × (a + a + 2) = 1312
2×a + 2 = 1312 : 2
2×a + 2 = 656
2×a = 656 - 2
2×a = 654
a = 654 : 2
a = 327 (primul numar)
a+2 = 327 + 2 = 329 (al 2-lea numar)
Verificam:
2 × (327 + 329) = 2×656 = 1312
2×a + 2 = 1312 : 2
2×a + 2 = 656
2×a = 656 - 2
2×a = 654
a = 654 : 2
a = 327 (primul numar)
a+2 = 327 + 2 = 329 (al 2-lea numar)
Verificam:
2 × (327 + 329) = 2×656 = 1312
Fie a si b = a+2
2(a + b) = 1312
2(a + a + 2) = 1312
2a +2 = 656
2a = 654
a = 327
b = 329
2(a + b) = 1312
2(a + a + 2) = 1312
2a +2 = 656
2a = 654
a = 327
b = 329